Effect of Top Management Team Characteristics and Green Innovation on Firm Performance in Indonesia: Role of Carbon Emission Disclosure - Tjahjadi, Bambang; Soewarno, Noorlailie; Kamarudin, Khairul Anuar; Aldina, Sazkiya; Karima, Tsanya El; Sutarsa, Annisa Ayu Putri (International Journal of Energy Economics and Policy, 2023)
The purpose of this study is to investigate whether top management team (TMT) characteristics and green innovation (GI) affect firm performance, and if so, whether the effect is mediated by carbon emission disclosure (CED). This quantitative study employs the partial least square structural equation modeling (PLS-SEM) to test the hypotheses. The data were collected from the high-profile companies listed in the Indonesia Stock Exchange (IDX) for the 2015 - 2019 period. A mediating research framework was developed to explain the association among constructs. Using agency theory and sustainability theory (triple bottom line), the results show the following findings. First, TMT characteristics positively affect firm performance. Second, GI positively affects on firm performance. Third, CED partially mediates the effect of TMT characteristics on firm performance. Fourth, CED partially mediates the effect of GI on firm performance. The current study addresses the existing research gaps and debates in the previous studies in term of proposing a more comprehensive framework by adding CED as a mediating variable. This study also builds a new dataset and focuses on environmental issues in the Indonesian research setting as an emerging country and a two-tier governance system adopter.